TVGrid: Computação em grid em uma rede de TV Digital - Batista, Carlos Eduardo Coelho Freire (2008)
Voluntary computing platforms such as those deployed for the SETI@home project have proven that it is possible to harvest massive amounts of unused bandwidth and computing power available from computers connected to the Internet. In this work we present the TVGrid architecture to explore this idea in the context of a digital TV network. In the proposed architecture, a TV station runs a scheduler that uses the unused bandwidth in the digital TV broadcast channel to send processes of a parallel (tasks) application to digital TV receivers, which may run them using their unused capacity. The output of the processing performed by the receivers are later sent back to the TV station through a return channel (a connection to the Internet). The presented architecture comprises two approaches on task scheduling, which are specified and analyzed based on data collected on representative tests. The work thus aims to define a universe of applications for which TVGrid's architecture better fits.